Corporate Crime Announcement Effects On Stock Performance: An Empirical Study In Malaysia - Voon, Sze-Ling; Puah, Chin Hong; Harry, Entebang (SESRIC, 2008)
An in-depth investigation of the effects of announcement of corporate crime on firm performance focusing on stock market performance among public enterprises in Malaysia has been conducted. A sample of 7 large, established public companies charged for committing corporate crime by Securities Commission from the period of 1999 to 2005 in Malaysia were identified and examined. Using the event-study methodology proposed by Rao (1997), monthly average abnormal returns (AARs) and cumulative average abnormal returns (CAARs) for the sample of 8 announcements of separate crimes ranging from 12 months prior to and 6 months after the announcement dates are determined. Empirical result indicates that the stock market is informationally inefficient in Malaysia and investors do react to announcement of corporate crime.